Pengaruh Ekspor, Reksadana Syariah dan Utang Luar Negeri Terhadap Pertumbuhan Ekonomi Nasional Periode 2012-2020 - Nurwahida Nurwahida; Sugianto Sugianto; Nurul Jannah (ITB AAS INDONESIA Surakarta, 2022)
Economic growth is the development of activities in the economy that causes an increase in goods and services produced in the society so that the prosperity of the society increases. In this case, Exports, Sharia Mutual Funds, and Foreign Debt can be used as alternative financing/capital to form a just and prosperous economy for the society. This study aims to determine the effect of exports, sharia mutual funds, and foreign debt on national economic growth for the 2012-2020 period, either partially or simultaneously. This study uses the variables of Export, Islamic Mutual Funds, Foreign Debt, and National Economic Growth Period. The results of this study through multiple linear regression tests show that exports have a positive and significant impact on National Economic Growth for the 2012-2020 period. Sharia Mutual Funds have a positive and significant impact on National Economic Growth for the 2012-2020 period. Foreign Debt has a positive and significant impact on National Economic Growth from 2012-2020. Exports, Sharia Mutual Funds and Foreign Debt have a simultaneous effect of Rp. 0.960151 billion or 96% of the National Economic Growth for the 2012-2020 period. Keywords : National Economic Growth, Ekport, Shariah Mutual Funds, Foreign Debt.